52 Optimisation of a cell-based model for the characterisation of novel drug-free stent coatings. (May 2019) - Longhorn, Daniel; Currie, Susan; McCormick, Christopher
Abstract : Current pharmacological approaches aimed at improving stent designs are limited by their inability to reduce endothelial damage following stent placement and improve healing. Here, we consider in vitro approaches that could be used to assess the effects of novel anti-oxidant stent coatings on damaged endothelial cells following stent placement. Oxidative stress is a physiological response to inflammation and can result in activation of intracellular signalling molecule, leading to pathological effects. One such molecule is calcium/calmodulin dependent protein kinase IIδ (CaMKIIδ). Hyper-activation of CaMKII is known to be directly linked to disease progression in the heart and it has been implicated in endothelial dysfunction. It is therefore of interest to examine how novel drug-free stent coatings might reduce or reverse oxidative damage following stent placement and whether CaMKII may be a potential target. Our initial experiments have used human umbilical vein endothelial cells (HUVECs), challenged with inflammatory and oxidative stress as a model for future investigations with novel stent coatings. Novel stent-coatings were generated on 200 μm stainless steel wires (316L medical grade), and their antioxidant activity assessed at 8h and 24h using a DPPH (2, 2-diphenyl-1-picrylhydrazyl) colorimetric assay and expressed as a percentage of scavenged to total radicals. Antioxidant activity was observed from the novel coatings, with 45 ±1.8% and 87 ±3.2% of radicals scavenged at 8 and 24 h respectively (one way ANOVA, n=3, p<0.05). Antioxidant activity was sustained over 5 days. HUVECs were cultured onto coated stainless steel strips and imaged using immunofluorescence to assess their attachment and viability. To model pro-inflammatory and pro-oxidative stress conditions, HUVECs were treated with IL-1β; which is known to be elevated in both conditions. ROS generation in HUVECs in response to IL-1β (3–10ng/ml; 1–6h) stimulation was assessed using a DCFDA (2', 7'–dichlorofluorescin diacetate)-based assay kit (Abcam, UK). IL-1β stimulated ROS production in a time and dose dependant manner with optimal effects at 3 ng/ml after 6 hours (3.3 ±0.73-fold increase between stimulated and unstimulated cells, one way ANOVA, n=3, p<0.05). Parallel assessment using quantitative immunoblotting of CaMKIIδ in HUVECs showed the enzyme was expressed and that activation (via phosphorylation or oxidation) can be detected. Increased phosphorylation of P65 in response to IL-1β (10ng/ml; 15 min-6h) stimulation was also detected, indicating increased pro-inflammatory signalling. In conclusion, we have established an effective cell-based model for mimicking the oxidative stress that can occur following stent placement and identified CaMKIIδ as a target protein. This approach will be applied to other more physiologically relevant cell types and may be used to examine the desired therapeutic effects of novel stent coatings in vitro. Conflict of Interest: N/A